High‐Throughput Bioassays using "Dip‐and‐Go" Multiplexed Electrospray Mass Spectrometry. (23rd October 2019) - Wei, Zhenwei; Xie, Zhuoer; Kuvelkar, Reshma; Shah, Vinit; Bateman, Kevin; McLaren, David G.; Cooks, R. Graham
Abstract: A multiplexed system based on inductive nanoelectrospray mass spectrometry (nESI‐MS) has been developed for high‐throughput screening (HTS) bioassays. This system combines inductive nESI and field amplification micro‐electrophoresis to achieve a "dip‐and‐go" sample loading and purification strategy that enables nESI‐MS based HTS assays in 96‐well microtiter plates. The combination of inductive nESI and micro‐electrophoresis makes it possible to perform efficient in situ separations and clean‐up of biological samples. The sensitivity of the system is such that quantitative analysis of peptides from 1–10 000 nm can be performed in a biological matrix. A prototype of the automation system has been developed to handle 12 samples (one row of a microtiter plate) at a time. The sample loading and electrophoretic clean‐up of biosamples can be done in parallel within 20 s followed by MS analysis at a rate of 1.3 to 3.5 s per sample. The system was used successfully for the quantitative analysis of BACE1‐catalyzed peptide hydrolysis, a prototypical HTS assay of relevance to drug discovery. IC50 values for this system were in agreement with LC‐MS but recorded in times more than an order of magnitude shorter. Abstract : Ein Multiplex‐System, das induktives Nanoelektrospray und Mikroelektrophorese integriert, wurde für Hochdurchsatz‐Bioassays entwickelt. Das System verfügt über eine extrem hohe Empfindlichkeit und Screeningraten von 1.3–3.5 s pro Probe.